Trimethylamine N-oxide attenuates high-fat high-cholesterol diet-induced steatohepatitis by reducing hepatic cholesterol overload in rats - Zhao, Ze-Hua (World J Gastroenterol, 2019)
BACKGROUND: Trimethylamine N-oxide (TMAO) has been shown to be involved in cardiovascular disease (CVD). However, its role in nonalcoholic steatohepatitis (NASH) is unknown. AIM: To determine the effect of TMAO on the progression of NASH. METHODS: A rat model was induced by 16-wk high-fat high-cholesterol (HFHC) diet feeding and TMAO was administrated by daily oral gavage for 8 wk. RESULTS: Oral TMAO intervention attenuated HFHC diet-induced steatohepatitis in rats. Histological evaluation showed that TMAO treatment significantly alleviated lobular inflammation and hepatocyte ballooning in the livers of rats fed a HFHC diet. Serum levels of alanine aminotransferase and aspartate aminotransferase were also decreased by TMAO treatment. Moreover, hepatic endoplasmic reticulum (ER) stress and cell death were mitigated in HFHC diet-fed TMAO-treated rats. Hepatic and serum levels of cholesterol were both decreased by TMAO treatment in rats fed a HFHC diet. Furthermore, the expression levels of intestinal cholesterol transporters were detected. Interestingly, cholesterol influx-related Niemann-Pick C1-like 1 was downregulated and cholesterol efflux-related ABCG5/8 were upregulated by TMAO treatment in the small intestine. Gut microbiota analysis showed that TMAO could alter the gut microbial profile and restore the diversity of gut flora. CONCLUSION: These data suggest that TMAO may modulate the gut microbiota, inhibit intestinal cholesterol absorption, and ameliorate hepatic ER stress and cell death under cholesterol overload, thereby attenuating HFHC diet-induced steatohepatitis in rats. Further studies are needed to evaluate the influence on CVD and define the safe does of TMAO treatment.